SEXUAL ORIENTATION MYTHS: DOES THEOLOGICAL EDUCATION AFFECT SEXUAL ORIENTATION MYTHS? - Hacer ÜNVER; İpek TURAN (Rojan GÜMÜŞ, 2021)
Sexual myths differ from one culture to the next, and one society to the next and they can even differ regionally within the same culture. The aim of this study is to determine the sexual orientation myths of university students studying theology. The study was conducted between February and June 2020 at three faculties of a state university in Eastern Anatolia, Turkey. This descriptive study was conducted with 582 students studying at three faculties. The data were collected by using the Personal Information Form, Sexual Orientation Myths Scale. In our study, there was no significant difference between the sociodemographic characteristics of the students who received and did not receive religious education in terms of sexual myths (p<0.05). It was determined in the study that there was a statistically significant difference between the sexual orientation myths of the students studying and not studying theology (p<0.001). This study's findings are important because they would guide future studies.